CORRELATION BETWEEN CYTOKINE CONTENT IN LYMPH OF THORACIC LYMPH DUCT AND MESENTERIC LYMPH NODE STRUCTURAL TRANSFORMATIONS IN EXPERIMENTAL MAMMARY TUMOR AND CHEMOTHERAPY - O. V. Kazakov; T. V. Rayter; A. F. Poveshchenko; N. B. Orlov; O. V. Poveshchenko; A. V. Kabakov; A. P. Lykov; I. I. Kim; N. A. Bondarenko; D. N. Strunkin; V. I. Konenkov (Сибирский научный медицинский журнал, 2019)
The aim of the study was to fulfill correlation analysis of morphometry of the mesenteric lymph nodes and the concentration of cytokines in the lymph of the thoracic duct in breast cancer induced by intramammary administration of N-methyl-N-nitrosourea, chemotherapy according to the CMF scheme (cyclophosphamide, methotrexate, 5-fluorouracil). The results of the study. At breast cancer revealed positive correlation: in the germinative centers and medullary cords of cytokine IL-5 with mitotically dividing cells, chemokines MIP-1α with average lymphocytes, in the germinative centers of immunoblasts with cytokine GRO/KC, in the paracortical zone chemokine MCP-1 with macrophages, reticular cells with IL-6 and M-CSF, in the medullary sinuses chemokine GRO/KC with small lymphocytes and mature plasma cells (number which decreases). All this may indicate the activity of the local immune response in the lymph nodes aimed on the antitumor protection. After chemotherapy of breast cancer, compared with breast cancer without treatment, revealed positive relationship, which may indicate increased immunomodulatory and antitumor actions of cytokines: correlation of interferon IFNγ with small lymphocytes (number which increased) and macrophages in the germinative centers and mitotically dividing cells in the medullary cords, correlation in the germinative centers of immunoblasts with MIP-1α and increased of number small lymphocytes in T-dependent zone lymph nodes, correlation in medullary cords of interleukin IL-17 with mature plasma cells (number which increased) , correlation of interleukin IL-18 with mature plasma cells in medullary sinuses. Conclusion. Study of the correlation of the concentration of cytokines in the lymph of the thoracic duct with structural changes in the mesenteric lymph nodes revealed dependencies aimed at increasing the immunomodulating and antitumor effects of cytokines.